2018
DOI: 10.1088/2053-1583/aab56a
|View full text |Cite
|
Sign up to set email alerts
|

Sub 20 meV Schottky barriers in metal/MoTe 2 junctions

Abstract: The newly emerging class of atomically-thin materials has shown a high potential for the realisation of novel electronic and optoelectronic components. Amongst this family, semiconducting transition metal dichalcogenides (TMDCs) are of particular interest. While their band gaps are compatible with those of conventional solid state devices, they present a wide range of exciting new properties that is bound to become a crucial ingredient in the future of electronics. To utilise these properties for the prospect … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…For instance, unipolar n ‐type, p ‐type, as well as ambipolar characteristics were measured in the MoTe 2 FETs, which are irrelevant to the work functions of the contact metals. [ 8–12 ] Furthermore, a study reported a weak Fermi level pinning at the metal–MoTe 2 interface, [ 13 ] whereas others argued a strong pinning with a factor as small as 0.07. [ 14 ] These inconsistencies are not well understood and set obstacles to the practical applications of this material in electronics.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, unipolar n ‐type, p ‐type, as well as ambipolar characteristics were measured in the MoTe 2 FETs, which are irrelevant to the work functions of the contact metals. [ 8–12 ] Furthermore, a study reported a weak Fermi level pinning at the metal–MoTe 2 interface, [ 13 ] whereas others argued a strong pinning with a factor as small as 0.07. [ 14 ] These inconsistencies are not well understood and set obstacles to the practical applications of this material in electronics.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the possible effect of reduced MoTe 2 channel thickness on n-type doping efficiency, we also speculate that the polarity switching from n- to p-type in thinner layers may be caused by the modulation of Schottky barrier height (SBH) and corresponding band alignment and band-bending at the metal/MoTe 2 interface. The effective barrier height for Ti, Cr, and Pd contacts are 41.1, 40.3, and 10.2 meV, respectively [41,42].…”
Section: Resultsmentioning
confidence: 99%
“…A 2 is also affected by the effective mobility of the charge carriers. As V g2 approaches the subthreshold region of the transfer curve, the current transport becomes limited by thermionic emission over the Schottky barrier [30], thus changing A 2 . The changes in the device conductivity can be modeled, to a first approximation, as a linear perturbation in the mobility δμ, so μ a = μ b + δμ.…”
Section: B the Energy Dispersive Spectroscopy Techniquementioning
confidence: 99%